Biofilm Alterations on the Stepwise Acquisition of Fluconazole-resistant Candida Albicans Isolates - Na-Na Song; Guan-Yu Qian; Hai-Lin Zheng; Xiao-Wei Zhou; Huan Mei; Dong-Mei Li; Xiao-Fang Li; Wei-Da Liu (Wolters Kluwer Health, 2022)
Objectives:. By assessing and comparing the phenotypic changes on the stepwise acquisition of fluconazole resistant Candida albicans isolates, we could find and describe the relationship between drug resistance and biofilm formation ability in a series of clonal strains. Methods:. We performed antifungal susceptibility of five drugs (fluconazole, itraconazole, voriconazole, caspofungin and amphotericin B) to further verify the antifungal activity of the six isolates in vitro. Then we combined hyphal formation assay, cell surface hydrophobicity test positively related to adherence ability, and biofilm assays in vitro to observe and compare the phenotypic characteristics of our six clonal strains. Results:. Biofilm capability is enhanced for four drug- intermediate strains, whereas the initial susceptible strain and the final resistant strain are both poor in adherence, hyphal growth and biofilm formation. Conclusions:. It was suggested that the biofilm formation ability were not absolutely related to the degree of fluconazole resistance.